Analisis Skala Ekonomi dalam Kerangka Optimalisasi Kinerja Credit Union Indonesia - Kusumajati, Titus Odong (Journal of Business Management Education (JBME), 2021)
This research aims at revealing the level of economies of scale of Credit Union in Indonesia, whether it is increasing return to scale, constant return to scale, or decreasing return to scale. It is a quantitative research in nature using multiple regression technique for data analysis. Data of this research was collected from the database of BKCU Kalimantan. Model presented and tested in this research was adapted from the cost function model of Benston-Bell-Murphy previously derived from Cobb-Douglass production function, adjusted to the condition of data of Credit Union in Indonesia which is characterized by limited data availability. The analysis found model applies for the case of Indonesia is Log C = 0.415 + 0.917 Log Q + 0.098 Log Pi + µ. In general, the model shows that the operational costs of Credit Union in Indonesia is influenced by the amount of credit distributed and the orientation of involvement of Credit Union member in the core business of Credit Union. Further, since the coefficient of b1 is less than 1 (b11), it can be concluded that the level of economies of scale of Credit Union in Indonesia is increasing return to scale.